Delivering a better natural environment? The Agriculture Bill and future agri-environment policy. (March 2019) - Rodgers, Christopher
This article reviews the options for delivering a new approach to agricultural support post-Brexit, and in particular the development of a new approach to delivering environmental protection and biodiversity improvement through future farming policy. It considers the options for developing a policy based on 'public money for public goods', and argues for the development of an approach based on payment for the ecosystem services provided by land management and by farming. If a 'payment for ecosystem services' approach is to be successful, however, careful consideration must be given to the reform of land tenure law in order to secure a stable platform for the long term management of ecosystems and landscapes. And new legal models will be needed for capturing multi-party obligations for the purchase and sale of ecosystem services. Brexit offers many opportunities for developing a new and innovative approach to agri-environmental policy, but the development of a market for the sale and purchase of the important ecosystem services provided by agriculture will present significant challenges.